وسائل البيان عند الجاحظ: الحال التي تُسمى نِصْبَةً نموذجاً (Journal of Faculty of Education, 2021)
This research deals with the types of semantic indicators in ALJahiz in general, and then it concentrates on the study of AL Nisba, which is situation semantics. The situation semantics- Nisba as defined by ALJahiz, is the situation articulating without a word; and pointing without a hand. The importance of studying the Nisba lies in the great impact it has on explaining meanings conveyed through it to humans. It also articulates the dead, rigid, silent and inexpressible meanings.To explain its importance, I have carefully tracked and explored it, citing evidence from ALJahiz, and then I added a number of evidences from the Holy Quran as well as prose and poetry evidences, which point to the importance of this means among other types of semantic indicators. Also, this research shows the extreme impact that the Nisba has on human soul by communicating some vital meanings to it.
Keywords: وسائل البيان; الجاحظ